Studytube: Educational Bloggers in the Higher Education Ecosystem - K. R. Romanenko; A. Yu. Makareva (Moscow Polytechnic University, 2023)
The article examines a new non-traditional actor in higher education: educational bloggers "studytubers" who being students themselves record informal and non-professional videos on the topic of learning, productivity, popular science, and education in general. The objectives of this study included a description of the phenomenon of the studytube itself, its history, context, specifics, then in revealing the ways educational bloggers work and, finally, in fixing its role in the ecosystem of higher education. The phenomenon of studytube was considered through an ecosystem approach, the framework of the "participatory culture", and the concept of "micro-celebrity". It was empirically studied through the methodology of digital ethnography and methods of nonparticipant observation, visual analysis of video materials, thematic analysis of texts. The results showed the main thematic repertoire of the educational bloggers, the stylistic features of their work, the affective nature of the work of educational bloggers, ways of interacting with subscribers, and monetization models. Recommendations are also offered to universities for the involvement of the studytube community into the development of the university environment.